Comparison of velocity distribution in turbulent diffusion jet given by the integral model and code CFD FLUENT 6.0 - Ga, Bui Van; Loan, Pham Thi Kim; Quang, Nhan Hong (Vietnam Journal of Mechanics, 2005)
Integral model is simple in utilization, low in CPU time calculation, suitable for a lot of practical applications of turbulent diffusion jet. However the assessment of accuracy of the model should be carried out by experimental data and by results of available multidirectional codes. The present paper shows the comparison of velocity profiles given by the integral model and the CFD FLUENT 6.0 Code. The difference in results given by the two models is lower than 10% when Reynolds number at the exit nozzle below 5000.